2006
DOI: 10.1016/j.asr.2006.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated microgravity on oxidation-sensitive gene expression in PC12 cells

Abstract: Oxygen utilization by and oxygen dependence of cellular processes may be different in biological systems that are exposed to microgravity (micro-g). A baseline in which cellular changes in oxygen sensitive molecular processes occur during micro-g conditions would be important to pursue this question. The objective of this research is to analyze oxidation-sensitive gene expression in a model cell line [rat pheochromocytoma (PC12)] under simulated micro-g conditions. The PC12 cell line is well characterized in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…It is probably based on our current results that enhanced activity of NF- κ B under MG as compared with DC will lead to differential regulation of down-stream gene networks precipitating some of the physiological changes observed under conditions of microgravity. This claim is also supported by our recent study using DNA microarrays to show that genes involved in oxygen utilization and metabolic processes were significantly dysregulated under micro-g conditions as compared with unit-g conditions [6]. The present results let us conclude that simulated micro-g conditions regulated the translocation of a prevailing oxygen-sensitive transcription factor, NF- κ B in a cardiomyocyte cell line.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…It is probably based on our current results that enhanced activity of NF- κ B under MG as compared with DC will lead to differential regulation of down-stream gene networks precipitating some of the physiological changes observed under conditions of microgravity. This claim is also supported by our recent study using DNA microarrays to show that genes involved in oxygen utilization and metabolic processes were significantly dysregulated under micro-g conditions as compared with unit-g conditions [6]. The present results let us conclude that simulated micro-g conditions regulated the translocation of a prevailing oxygen-sensitive transcription factor, NF- κ B in a cardiomyocyte cell line.…”
Section: Resultssupporting
confidence: 87%
“…The physiological effect of NF- κ B activation can be further investigated with focus on specific target genes. 2 For instance, c-myc, NADH quinine oxidoreductase, and glucose-6-phosphate 1-dehydrogenase were suggested to be MG regulated from our preliminary DNA microarray results [6] and are transcriptional target genes of NF- κ B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study showed that exposure to SMG induces cellular senescence in PC12 cells via an increased oxidative stress [11]. In particular, genes involved in oxidoreductase activity are the ones most significantly differentially expressed [12] under conditions of SMG produced either by a rotating wall bioreactor with a high aspect ratio vessel or by a clinostat. All these results indicate that there is increased oxidative stress in neuronal cells subjected to microgravity.…”
Section: Introductionmentioning
confidence: 99%
“…The current parametric results can be used to minimize costly cell culture experiments for optimizing conditions of cell/bead suspension in the bioreactor (Kwon et al, 2006). In addition, the present results on numerical prediction of the distribution of cell/microcarrier beads and the concentration of biochemical components such as oxygen in the bioreactor may play a significant role in the design of new bioreactors to study optimized suspension cultures of cells and tissues.…”
Section: Discussionmentioning
confidence: 92%